(untitled) (Raparin Journal of Humanities (RJH), 2024)
The research aims to: - To identify the differences between the two tests of the vertical jump of stability and the platform of the jumping platform in measuring the explosive power of the two legs of the female volleyball players. - Identifying the relationship between the two vertical jump tests of stability and the platform jumping device in measuring the explosive power of the two legs in female volleyball players. As for the research hypothesis:- -There are statistically significant differences between the standing vertical jump tests and the jumping platform device in measuring the explosive power of the legs in female volleyball players. - There is a significant correlation between the two standing vertical jump tests and the jumping platform device in measuring the explosive strength of the legs in female volleyball players. The research community was determined by the intentional method of the players of the first degree of volleyball in the Kurdistan Region / Iraq.The research sample was determined by the random method from the research community, which consisted of players from these clubs (Hajiaoa, Rania, and Tactac,koya University Team) which in total were 37 players, One female player was excluded from the Hajiao Club due to not attending the test day, and (6) female players from the Koya University team were excluded because of their participation in the reconnaissance experiment. Thus, the size of the final sample reached 30 players out of 30 players, with a rate of 81.01%. The researchers used the descriptive approach in a comparative study method. And the correlations, and after obtaining the results, they were discussed in a scientific manner supported by the sources to achieve the research goals. In light of the research results, the researchers reached the following Conclusions: - There is a correlation between the springboard mat test and the standing vertical jump test in their measurement of the explosive strength of the legs in female volleyball players. - There are differences between the springboard mat test and the vertical stability jump test in their measurement of the explosive power of the legs in female volleyball players, and in favor of the springboard mat test.